A polissemia das alforrias: significados e dinâmicas das libertações de escravos nas Minas Gerais setecentistas - Douglas Lima de Jesus (2014)
The aim of this study is to investigate the meanings and the dynamics of the notarized manumissions, in the Comarca do Rio das Velhas, especially in the region of the Town of Sabará, Minas Gerais, among 1711 and 1740. To achieve the proposed objective, comparative and qualitative methodologies have been used, in a project that demanded integral reading and transcription of the registers found. The analysis do not aim the demographic and economic targets of the manumissions, but the understanding of its legal and daily aspects, connected to a great extent, to slavery experiences of other times and regions. From this point of view, unnoticed questions in other research models, that aim to answer quantitative questions, are emphasized. This has allowed to identify two modalities of notarized manumissions: cartas (letters) and escrituras (scriptures). It also allowed the understanding of the importance of the documentation register and of the characters involved in the process. In the effort to a broader contextualization of the subject, throughout the research, aspects like different perceptions about the manumissions and identities and origins of the freedmen occupy relevant spaces.